A Study of Malposition of Central Venous Catheter – A Comparative Study between Ultrasound Guided and Anatomical Landmark Technique - Rajbanshi, Lalit Kumar; Karki, Sambhu Bahadur; Arjyal, Batsalya (Birat Journal of Health Sciences, 2018)
Introduction: Central venous catheterization is a routine procedure for long-term infusion therapy and central venous pressure measurement. Sometimes, the catheter tip may be unintentionally placed at the position other than the junction of superior vena cava and right atrium. This is called malposition and can lead to erroneous pressure measurement, increase risk of thrombosis, venous obstruction or other life threatening complications like pneumothorax, cardiac temponade. Objectives: This study aimed to observe the incidence of the malposition and compare the same between ultrasound guided catheterization and blind anatomical landmark technique. Methodology: This study was a prospective comparative study conducted at the intensive care unit of Birat Medical College and Teaching Hospital for two-year duration. All the catheterizations were done either with the use of real time ultrasound or blind anatomical landmark technique. The total numbers of central venous catheterization, the total incidences of malposition were observed. Finally the incidences were compared between real time ultrasound guided technique and blind anatomical landmark technique. Results: In two-year duration of the study, a total of 422 central venous cannulations were successfully done. The real time ultrasound was used for 280 cannulations while blind anatomical landmark technique was used for 162 patients. The study observed various malposition in 36 cases (8.5%). The most common malposition was observed for subclavian vein to ipsilateral internal jugular vein (33.3%) followed by subclavian to subclavian vein (27.8%) and internal jugular to ipsilateral subclavian vein (16.7%). In four patients the catheter had a reverse course in the internal jugular vein while the tip was placed in pleural cavity in three cannulations. There was coiling of the catheter inside left subclavian vein in one patient. The malposition was significantly reduced with the use of the real time ultrasound (P< 0.001). However there is no significant difference in the incidence of the various malposition between ultrasound guidance technique and blind anatomical landmark technique when compared individually. Conclusion: The malposition of the central venous catheter tip was common complication with the overall incidence of 8.5%. The most common malposition was subclavian vein to internal jugular vein. The use of real time ultrasound during the catheterization procedure can significantly reduced the risk of malposition. Birat Journal of Health Sciences Vol.2/No.3/Issue 4/Sep- Dec 2017, Page: 277-281